THE RELATIONSHIP BETWEEN SOCIAL SUPPORT AND RESILIENCE TO BURNOUT IN VOCATIONAL TEACHERS - Cornelia, Citra; Widyastuti, Widyastuti (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to determine the relationship between social support and resilience to burnout in Vocational High School teachers in Sidoarjo. Method: This study used a correlational quantitative method involving 129 vocational school teachers in Sidoarjo as samples. Results: The results showed that there was a weak positive relationship between social support and burnout, meaning that the higher the social support, the lower the burnout level. However, no significant relationship was found between resilience and burnout. This study concluded that social support plays an important role in reducing the risk of burnout in vocational teachers, while resilience did not show a significant effect. Novelty: This study suggests further research with a larger and more diverse sample and considering other factors that may affect burnout.